2011
DOI: 10.1517/14728222.2011.609557
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α3β1 as a breast cancer target

Abstract: INTRODUCTION Integrin receptors for cell adhesion to the extracellular matrix have important roles in all stages of cancer progression and metastasis. Since the integrin family was discovered in the early 1980’s, many studies have identified critical adhesion and signaling functions for integrins expressed on tumor cells, endothelial cells, and other cell types of the tumor microenvironment, in controlling proliferation, survival, migration, and angiogenesis. In recent years, the laminin-binding integrin α3β1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 112 publications
1
54
0
Order By: Relevance
“…These findings have important implications for understanding how integrins, in particular a3b1, contribute to cancer progression through gene regulation that drives malignant cell behavior and tumor angiogenesis, and how this regulation might be exploited in therapeutic strategies to inhibit cancer progression. Indeed, both a3 and Cox-2 are expressed highly in human breast cancers (Morini et al, 2000;Singh-Ranger et al, 2008;Subbaram and DiPersio, 2011), and our data mining analysis revealed that both are correlated with disease progression in human breast cancer (supplementary material Fig. S1).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…These findings have important implications for understanding how integrins, in particular a3b1, contribute to cancer progression through gene regulation that drives malignant cell behavior and tumor angiogenesis, and how this regulation might be exploited in therapeutic strategies to inhibit cancer progression. Indeed, both a3 and Cox-2 are expressed highly in human breast cancers (Morini et al, 2000;Singh-Ranger et al, 2008;Subbaram and DiPersio, 2011), and our data mining analysis revealed that both are correlated with disease progression in human breast cancer (supplementary material Fig. S1).…”
Section: Discussionmentioning
confidence: 84%
“…It is well known that Cox-2 plays important roles in driving tumor angiogenesis and breast cancer progression, and clinical investigations of breast and other cancers have indicated that treatment with Cox-2 inhibitors might improve survival in some cancer patients (Harris, 2009;Howe, 2007;Singh-Ranger et al, 2008). However, adverse side effects have been associated with direct inhibitors of Cox-2, and indirect suppression of Cox-2 through targeting of integrin a3b1, or its downstream effectors, might avoid these side effects (Subbaram and DiPersio, 2011). Therefore, further investigation of the pathways whereby a3b1 controls AEU and/ or suppresses NMD might lead to new therapeutic strategies to block these pathways in tumor cells; thereby reducing gene expression of Cox-2 (and other pro-cancer genes) through enhanced NMD and providing protective effects in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the integrin-blocking agent Cilengitide, an RGD mimetic, has shown promise in clinical trials involving the treatment of recurrent glioma. 165,166 It is well known that wound healing and skin carcinogenesis share similarities regarding both epidermal cell function and microenvironmental factors that drive each process, 57 and integrin-targeting therapies are relevant to the treatment of chronic wounds for many of the same reasons that they are relevant to the treatment of cancer. For example, we have already discussed how roles for some integrins within the stem cell compartment may be important during both wound re-epithelialization and skin carcinogenesis (see Epidermal proliferation).…”
Section: Future Directions Exploiting Integrins As Therapeutic Targetmentioning
confidence: 99%
“…Interactions between FN and integrins play an important role in tumor cell migration, invasion and metastasis (25). αvβ6 integrin was found to be significantly upregulated in certain cancer types including colon (18,26) and ovarian carcinoma (27) and in early stage non-small cell lung cancer (NSCLC) (28).…”
Section: Discussionmentioning
confidence: 99%